2012
DOI: 10.3126/hren.v10i3.7140
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude on sexual behaviour among school adolescents

Abstract: Background: Most of the adolescents of remote areas of Nepal lack the basic knowledge about sex due to which they are suffering from various sex related problems. Objective: To identify the level of knowledge and attitude about sex, sexually transmitted infections (STIs) especially HIV/AIDS and their prevention in adolescents. Methods: This crosssectional study was conducted in various secondary schools of Dhankuta district involving 200 adolescent students aged between 13 to19 years. Collected data was entere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…In which only 29.4 % of participants knew. The present study found that 62.6 % of adolescents knew about safer sex, which differs from an earlier survey of Sah, et al, [12] where only 26% of respondents had proper knowledge about safer sex. 77.8% of adolescents had knowledge that the emergency contraception that can be taken within 72 hours of unprotected sex.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In which only 29.4 % of participants knew. The present study found that 62.6 % of adolescents knew about safer sex, which differs from an earlier survey of Sah, et al, [12] where only 26% of respondents had proper knowledge about safer sex. 77.8% of adolescents had knowledge that the emergency contraception that can be taken within 72 hours of unprotected sex.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the adolescents of remote areas have a lack of the basic knowledge about sexual health in Nepal and due to which they have been suffering from various sexual health-related issues [12]. Health workers and the teacher are reluctant to discuss the problems.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast to this study, a study conducted in Dhankuta district of Nepal revealed 16% of adolescents preferred premarital sex. 10 In the study, attitude on premarital sex was high in boys (46% versus 34%) and government school students than in private school students (57% versus 33%). Again in contrast to the study, it was found that only 27.9 % of males and 7.2 % of females approved premarital sex and 54% of males and 74 % of females disapproved premarital sex in two cities of India.…”
Section: Discussionmentioning
confidence: 76%
“…Another study was conducted in Dhankuta district of Nepal which revealed that 16% of adolescents preferred premarital sex. [7] A similar study conducted in Pokhara Valley of Nepal showed that 41% of the students (which included both boys and girls) did not mind having premarital sex. [8] It has been reported in a study conducted by Jain et al [9] that 22.7% of the participants felt that it was ok to have sex with different people and 39.72% felt premarital sex gives popularity.…”
Section: Discussionmentioning
confidence: 99%